2021
DOI: 10.1108/apjml-09-2020-0641
|View full text |Cite
|
Sign up to set email alerts
|

Please do not disturb: the effect of Zero-Contact Marketing on Korean consumers' decision-making process

Abstract: PurposeThis study examines the effectiveness of Zero-Contact Marketing that minimizes contact between employees and consumers in marketplaces by adopting an integrated research framework of motivation theory, servicescape model and the theory of reasoned action (TRA).Design/methodology/approachThis study randomly collected 314 respondents through an online survey in May 2020 in South Korea. Structural equation modeling (SEM) assessed the overall hypothetical research model.FindingsZero-Contact Marketing facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…(2020a) showcased the critical role of two-way interaction between customers and brands in influencing consumers' behavioural intentions. Revisit intentions are defined as the customer's intention and willingness in returning to a specific store based on their assessment of the retailer's attributes (Park et al. , 2021; Jeong and Kim, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…(2020a) showcased the critical role of two-way interaction between customers and brands in influencing consumers' behavioural intentions. Revisit intentions are defined as the customer's intention and willingness in returning to a specific store based on their assessment of the retailer's attributes (Park et al. , 2021; Jeong and Kim, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similarly, Cheung et al (2020a) showcased the critical role of two-way interaction between customers and brands in influencing consumers' behavioural intentions. Revisit intentions are defined as the customer's intention and willingness in returning to a specific store based on their assessment of the retailer's attributes (Park et al, 2021;Jeong and Kim, 2019). These intentions have been frequently used to anticipate the level of customer satisfaction towards a certain retailer (Maxham and Netemeyer, 2002).…”
Section: Revisit Intentionmentioning
confidence: 99%
“…Moreover, high satisfaction with online shopping showed that consumers are likely to continue to buy online during the COVID-19 pandemic (Kazancoglu & Demir, 2021). One of the main consumer goals during the pandemic has been to preserve health and reduce the possibility of getting the virus by limiting contact with others (Park et al, 2021). Some studies have demonstrated (Fihartini et al, 2021) that the health risk was has been a more dominant influence on online shopping behaviour than other variables of online retail ethics.…”
Section: Consumer Beehaviourmentioning
confidence: 99%
“…Within the consumer behaviour field, the decision-making process has a relevant role, and, as stated by Pantano et al (2020), it is influenced by different levels of risk aversion and perception. The health risk (Fihartini et al, 2021) and the fear of social contact (Chang, 2021), led consumers towards a "zero contact" (Park et al, 2021) shopping behaviour. Therefore, as in other stressful circumstances (Mathur et al 2003;Guthrie et al, 2021) the consumption lifestyle changed, and physical interaction was limited in favor of digital interaction.…”
Section: How the Covid-19 Pandemic Is Changing The Retail Landscape?mentioning
confidence: 99%
“…Technology is the core enabler of the strategies related to the 6Ps of retailing (retail place and supply chain management, product, pricing, promotion, personnel, and presentation) and to maintain the service capacity of sustainable operations in retail stores (Milman et al, 2020;Zhou, 2020;Chang, 2021;Gupta et al, 2021;Jafarzadeh et al, 2021). Online shopping by mass consumers has increased significantly during the pandemic (Showrav et al, 2021) and retailers should develop strategies to protect them and understand that the use of technology will become the new normal (Khaled et al, 2020;Northington et al, 2021;Park et al, 2021). Digital and social media marketing strategies, including campaign development, implementation, measurement and results and an immersive in-store experience offered to customers could increase purchases within physical store locations when social distancing directives for COVID-19 are fully lifted and business returns to normal (Smith, 2020).…”
Section: The Impact Of Covid 19 On Retail Marketing Activitymentioning
confidence: 99%